EXPLORING MULTIMODAL APPROACHES IN STORYTELLING FOR LITERACY DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - Sirait, Asnita; Gunawan, Wawan; Radesman Lingga, Thomson; Siswantara, Yusuf; Lisdawati, Ida (English Review: Journal of English Education, 2025)
Improving students’ literacy has drawn various scholars’ attention as technology advances. This systematic literature review aims at investigating and synthesizing how multimodal approach is applied in the teaching of storytelling to improving students’ literacy. This study focuses on several aspects of multimodal applied in storytelling, such as components, media, objectives, skills improved, linguistic theories, and the complexity of the applied approach across different level of education. There are 71 articles collected to make a synthesis of storytelling which are published in range of 2017 to 2023. The selected articles are then compressed to 33 for articles based on the criteria of inclusion and exclusion. The study finds that the use of multimodal literacies in different level of study vary in the modes and media. In early educations, multimodal storytelling approach uses simpler components like audio and visual components but less digital tools. In the primary to secondary education, the combination of audio, visual and digital tool is balanced, while in higher to university education, multimodal approach is more complex with the combination of digital storytelling with linguistic theories such as MDA, social semiotics, and structural semiotics. This study is expected to provide other researchers or teachers a guideline of designing multimodal approach in storytelling classroom more deeply. By categorizing multimodal storytelling practices across educational level, this study offers practical guidance for educators to tailor their approaches to students’ developmental needs in literacy skills through storytelling and the selection of appropriate tools and techniques for diverse educational needs.